Leksikon Pakaian dalam Bahasa Jawa - Suharyanto Suharyanto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Language is underlyng the classification of experiences differently, and this classifications are not always realized by the speakers. The classification that appears in the language system reflect mind or psychology of speakers. The study aims to determine the classification the domain of clothin knowledge by Javanese speakers. This research using the etnosemantics theory. The results showed that domain of clothing knowledge in the Javanese language, as reflected in the lexicon used, classified according to two things, namely the physical characteristics and its function of clothing in the life.